Metaheuristic Algorithm Based Maximum Power Point Tracking Technique Combined With One Cycle Control For Solar Photovoltaic Water Pumping Systems - R, Nisha; Sheela K, Gnana (Frontiers in Energy Research, 2022)
Solar Photovoltaic Technology have become eminent in the world dueto its clean and abundant nature and can be effectively used for waterpumping applications. A Maximum Power Point Tracking method is indispensable to achieve the best benefit from photovoltaic systems. Conventional Maximum Power Tracking methods become successful onlyunder uniform irradiance conditions and fail to track the maximumpower under partial shading conditions. Hence, Nature Inspired Meta-heuristic algorithms were proposed to track the optimum power undervarying environmental conditions.This study proposes a method forimproving the performance of the Nature Inspired Maximum PowerPoint Tracking Algorithms by using a non-linear control technique calledOne Cycle Control. Based on the duty cycle obtained from the tracking algorithm the One Cycle Control technique generates pulses forthe DC-DC converter which is connected to a Brushless DC MotorPump system through a Voltage Source Inverter. The performanceof the proposed system under various partial shading conditions are validated using Cuckoo Search Algorithm, Particle Swarm Optimisation Algorithm and Grey Wolf Algorithm.Simulation results for variousshading patterns prove the supremacy of the system with respect toconvergence speed, tracking efficiency, robustness, steady state oscillations at Maximum Power Point and initial exploration oscillationsin comparison with systems without One Cycle Control. In addition the introduction of KY converter as DC-DC converter reducesthe output voltage ripple in the system. Thus the proposed systemwith One Cycle Control overcomes the disadvantages of the existing methods and can be effectively utilized for water pumping applications.